The effect of HIV status on clinical outcomes of surgical sepsis in KwaZulu-Natal Province, South Africa - Green, S; Kong, VY; Odendaal, J; Sartorius, B; Clarke, DL; Brysiewicz, P; Bruce, JL; Laing, GL; Bekker, W (Health and Medical Publishing Group, 2017)
Background. KwaZulu-Natal Province, South Africa (SA), has long been the epicentre of the HIV epidemic, but the impact of HIV co-infection on the clinical outcomes of emergency surgical patients with sepsis remains largely unknown. Objective. To review our experience with the management of patients with HIV co-infection and to compare the disease spectrum and outcome with those without HIV infection. Methods. A retrospective study was undertaken at the Pietermaritzburg Metropolitan Surgical Service (PMSS), SA over a 5-year period from January 2010 to December 2014. Results. A total of 675 patients with a documented surgical source of sepsis were reviewed. Of these, 332 (49%) were male, and the mean age was 46 (standard deviation 19) years. HIV status was known in 237 (35%) patients, 146 (62%) were HIV-positive and the remaining 91 (38%) were HIV-negative. Other than tuberculosis of the abdomen being significantly more common in HIV-positive than HIV-negative patients (10% v. 2%, p=0.033), there were no differences in the spectrum of diseases between the two groups. There were no significant differences in overall morbidity or mortality. When adjusted for CD4 counts, the mortality in HIV-positive patients with a CD4 count <200 cells/μL was 60% (15/25) and in those with a CD4 count >200 cells/μL it was 2% (2/101) (p<0.001). Conclusion. The clinical presentation and the spectrum of surgical sepsis in patients with HIV co-infection were not markedly different to those in patients who were not HIV-infected. HIV-infected patients with a CD4 count <200 cells/μL had a significantly higher mortality. Management approaches should not differ based solely on the HIV status of patients with surgical sepsis.